EFFECTS OF SUPPLEMENTING LACTIC ACID BACTERIA ON FECAL MICROBIOTA, TOTAL CHOLESTEROL,TRIGLYCERIDES AND BILE ACIDS IN RATS. - Zhimin, Jin; Hong-bo, Zhang; Xuehui, Jia; Qian, Yuan; Liga, Tong; Yan, Duan; Ye, Jin (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Probiotics (LAB) are normal components of the intestinal micro-flora in both humans and animals and its ingestion in decreasing the risk of atherosclerosis. In addition, the potential health effects of LAB were investigated by monitoring changes in intestinal micro-flora and lipid metabolism in a rat model. Materials and Methods: Rats were randomly assigned into four treatments and fecal samples were obtained on days 1, 3, 5, 9 and 14,to evaluate fecal micro biota, total cholesterol (TC), triglycerides (TG) and bile acids in rats (TBA). Results: The results indicated that Lactobacillus plantarum strain L.p X3-2B increased fecal lactic acid bacteria(LAB) and Bifidobacterium while resisting the growth of harmful bacteria. Viable counts of LAB and Bifidobacterium reached 8 log cfu/mL after feeding for 14 days. Fecal pH in the control group was high in comparison with the treatments at all times. Treatment increased the excretion of triglycerides (TG), total cholesterol (TC) and total bile acid (TBA). The results indicate that LAB and Bifidobacterium induce a positive correlation with fecal TC, TG and TBA and a negative correlation with fecal Enterobacteriaceae, Enterococcus and Escherichia coli. Conclusion: Lactic acid bacteria screened from Inner Mongolia native meat sausages in China had cholesterol-lowering effect.